Poisoned blade : a Court of Fives novel - Elliott, Kate, 1958- (Elliott, Kate, 1958- Court of Fives novel., 2016)
"Now a Fives Challenger, Jes travels the countryside to compete against adversaries of similar skill levels, using the opportunity to search for her missing twin sister, Bettany, only to be thrown into the center of the war that Lord Kalliarkos--the boy she still loves--is fighting against their country's enemies"--